The Carbon Footprint as a Key Indicator for Environmental Management Controllers: Towards Environmental Performance – A Literature Review - Kaoutar Bouchouit; Azzouz Elhamma (European Scientific Journal, ESJ, 2025)
Environmental considerations are increasingly critical for corporate sustainability and success. While businesses integrate environmental management into their strategies, the practical implementation of environmental management control systems, or “eco-control,” remains underexplored. This paper examines the conditions necessary for effectively integrating carbon footprint requirements and regulatory codes into eco-control systems. We articulate the importance of environmental performance objectives in addition to traditional performance objectives as core values of control management. Additionally, we highlight the pivotal role of environmental management controllers in aligning environmental sustainability with traditional business objectives. By measuring greenhouse gas emissions and developing strategies that are both economically viable and environmentally sound, controllers embed environmental objectives into core business processes. Despite challenges like capturing indirect emissions and the lack of standardized reporting methods, they have the potential to make sustainability a strategic component of corporate management. Future research should focus on enhancing their role by developing better tools and standardized methodologies for measuring environmental performance.